Covid-19 Pandemic and Volatility Spillover Effects on Foreign Exchange Rates - Kushwah, Silky Vigg; Negi, Pushpa (Indian Journal of Finance, 2024)
Purpose : The study aimed to examine the impact of COVID-19 on exchange rate volatility in five major emerging economies: the Indian rupee, Brazilian real, Mexican peso, Chinese yuan, and South African rand. Advanced statistical analysis techniques, including the GARCH (1,1) model and asymmetric volatility models, were employed to uncover significant insights. Design/Methodology/Approach : The influence of unfavorable COVID-19 news on exchange rate volatility in the five key emerging nations described above was examined using sophisticated statistical analytic approaches, such as the GARCH (1,1) model and asymmetric volatility models. Findings : The study found that past-day volatility greatly impacted current-day volatility, supporting the existence of the ARCH effect. Surprisingly, external independent variables—LBR, LCY, LMP, and LSR—demonstrated no significant impact on the volatility of LIR, highlighting susceptibility to internal shocks. The results of further using asymmetric volatility models to evaluate long-term consequences indicated that COVID-19 did not affect these variables. Exchange rate returns were not volatile even in the face of bad pandemic-related news. Practical Implications : The study enhanced the body of knowledge on COVID-19’s effects on currency exchange rates while offering managers and marketers useful advice on navigating currency volatility. Originality : In contrast to other research, this study contributed to the body of knowledge by examining the effects of COVID-19 on exchange rate volatility within important emerging markets using advanced statistical approaches. It sheds light on the intricate dynamics of currency changes during crises, providing new insights that are beneficial to scholars and experts in the field of international finance.